IPTEK BAGI MASYARAKAT (Ib.M) KELOMPOK USAHA PERALATAN DAPUR - Muhaimin Dimyati; Zainollah Zainollah; Hary Sulaksono (STIE Mandala Jember, 2014)
Kitchen ware made from aluminum and stainless - steel mostly produced by large corporations branded fraction by micro entrepreneurs. For microentrepreneurs faced many obstacles, among others, capital, market,supply chain of raw materials, human resources and labor. Inventory is one of the problems that continue to disrupt the production and marketing process. This is because the raw material supply chain does not guarantee the availability of raw materials needed. Solving problems of IBM partners mutually agreed , mainly to address thefundamental problem: how to manage the inventory of raw materials and how to manage finances micro-enterprises. Resolving the problem required dihadai various methods such as: is the method through application assistance for the implementation of Material Requirements Planning (MRP) and the method of Supply Chain Management (SCM), as well as training and mentoring management Cash Management and Accounting simple, and sharing the cost ofprocurement of production equipment in accordance the availability of funds. The end result of this activity is that the use of methods MRP and SCM method does not match the scale of the industry's only business partner households , adjustment method implementation is done by building long-term contracts with suppliers ofraw materials, raw material quality standards will be guaranteed by long-term contracts with supplier of raw materials, and there needs to be built from the Department of Trade and Industry District Jember.